RESPON ASAL BIBIT SETEK DAN JENIS MEDIA TANAM TERHADAP PERTUMBUHAN TANAMAN KRISAN (Chrysanthemum sp.) VAR. ARMITA PADA TAHAP AKLIMATISASI - Salsabilla, Nanda Aulia; Tiara, Dede; Maulida, Desi; Erfa, Lisa (Politeknik Negeri Lampung, 2024)
In vitro culture method can be used to obtain superior chrysanthemum seedlings. The objective of this research is to determine the origin of the cuttings and the best type of planting media for the growth of chrysanthemum seedlings at acclimatization stage. Data collection for this research was carried out in March-May 2024 at Lampung State Polytechnic Ornamental Plant Net House. This research used a Randomized Block Design (RAK) with two factors, namely origin of cuttings seedlings and type of planting medium with 6 treatment combinations which were repeated 4 times. The first factor are origin of the cutting seedlings (P1) top of the plant, and (P2) middle part of the plant. Meanwhile, the second factor are type of planting medium (M1) husk charcoal, (M2) goat pen compost, and (M3) cocopeat. The results of this research show that the use of shoot cuttings with cocopeat and charcoal husk planting media showed better results in all parameters.